Education on Stunting Prevention through the Piring Protein E-Book in Supporting Optimal Growth and Development of Toddlers in the Pondok Labu Community Health Center Working Area - Vini Yuliani; Sudiyati; Yunita Laila Astuti; Nurhayati; Vera Suzana Dewi Haris (Universitas STRADA Indonesia, 2026)
Stunting at an early age risk reducing educational achievement, decreasing cognitive abilities, and lowering income when the child reaches adulthood. In the working area of the Pondok Labu Community Health Center, three toddlers were identified with stunting, partly due to limited maternal knowledge regarding essential nutrition, particularly animal protein intake. This community service program aimed to improve mothers’ knowledge, attitudes, and feeding practices to support optimal toddler growth and development through education using the Piring Protein E-book.The activity was conducted for three months at Posyandu Jeruk 2 in the working area of Pondok Labu Community Health Center, South Jakarta, involving 35 mothers of toddlers using quota sampling. The methods included interactive counseling, distribution of the Piring Protein E-book through digital media, and self-monitoring. Measurements were carried out using pre-test and post-test assessments. The variables measured were mothers’ knowledge and attitudes using questionnaires, daily protein intake using a 24-hour food recall, and toddler nutritional status based on the height-for-age Z-score (HAZ). Data were analyzed using a paired sample t-test.The results showed a significant increase (p < 0.001) in mothers’ knowledge and attitudes, with the average knowledge score rising from 55.2 to 88.9. Improvements were also observed in toddler nutritional status based on the HAZ score. Education using the Piring Protein E-book proved to be an effective intervention to improve maternal nutritional literacy and support optimal toddler growth and development.